The compass - Stone, Josh; Ellis, John Spencer; Miller, Dan John; Greenlee, Marlow ([Mountville, PA] : Spencer Media Inc., 2008)
The Compass is a life transformation novel that will guide you on a journey of self-discovery. At the core of The Compass are specific lessons about belief systems and understanding who you really are in order to live out your destiny. Jonathan, the main character, escapes his suburban life after a tragedy that alters his plans for the future. Paralyzed by grief, he decides to journey across the globe in an effort to realign his inner compass
Title from title screen
Bonus DVD features: Teen Compass with Tami Walsh, Extras from the Exprerts, Al & Marilyn Sargent's Balance Compass
Executive producers, John Spancer Ellis ; editor, Paul Hoffman
DVD format
Keywords: Self-actualization (Psychology); Spiritual life -- Fiction; Religious fiction; Traffic accidents